The political economy of rural development in China: reflections on current rural policy - Flemming Christiansen; Heather Xiaoquan Zhang (University of Duisburg-Essen, Institute of East Asian Studies (IN-EAST), 2009)
The paper examines some of the main political economy dynamics of the policy initiatives on rural development that have been taken since 2003, and provides an overview of the main issues that they are addressing. The paper first outlines the major agrarian problems that have emerged over the recent decade and more, indicating their main political-economy causations, and then systematically analyses the prospects of the new policy initiatives to deal with them. Among the new policies the initiatives to reorganise the finance system through a reform of the roles of the county and a development of town and township governments to become points of delivery of public goods and social services are highlighted as particularly potent. Further importance is associated with reforms that strengthen the role of rural residents as citizens. The impact of the Chinese government's economic stimulus package in response to the ongoing global financial crisis is yet to become visible, but it is clear that the changes must be backed up with very substantial political and financial commitments.
Keywords: 330; rural policy; political economy; rural-urban relations; Ländliche Entwicklungsplanung; Agrarpolitik; Public Choice; Stadt-Land-Beziehung; Ländliche Entwicklung; China